Sustainable Development Strategy for Small Medium Industry Based on Ecology in Malang District - Purnomo, Purnomo; Sukoharsono, Eko Ganis; Yanuwiadi, Bagyo; Koderi, Koderi (Postgraduate School of Universitas Brawijaya, 2025)
Ecology-based Small and Medium Industries (SMEs) in Malang Regency are currently facing challenges related to environmental issues. Sustainable area development is the development of the SMEs area that purnomomachung@gmail.com the ecological dimension, the economic dimension, the social dimension, the infrastructure dimension, and the legal and institutional dimension. Sustainable development strategy to ensure the sustainability of future generations. The research objective is to provide natural resources according to ecological or environmental factors and improve an area or region's economic and social quality. The research method uses a qualitative approach. Development of small and medium-sized industrial estates based on superior products sourced from the availability of raw materials in an area. Industrial ecological zone for Small and Medium Industries (SMEs). The study's results link the availability of raw materials, the production process, and the community's consumer needs. Integrating processes in industrial estates that become a single unit can simplify the management of SMEs, increase industrial capabilities from waste management, marketing, licensing, and capitalization, and become a liaison for SMEs in the Malang Regency. Keywords: ecology, featured product, small and medium industry, sustainable development